If it's not what You are looking for type in the equation solver your own equation and let us solve it.
6+7x/7=-2
We move all terms to the left:
6+7x/7-(-2)=0
We add all the numbers together, and all the variables
7x/7+8=0
We multiply all the terms by the denominator
7x+8*7=0
We add all the numbers together, and all the variables
7x+56=0
We move all terms containing x to the left, all other terms to the right
7x=-56
x=-56/7
x=-8
| 3-x+5=2x-12+3x | | 9-^-3x+2=48 | | -(1+5p)=13-3p | | 11=x+108 | | 3k+12=2k+12 | | 1,2=3x-0,9 | | -0.333(9x+43)-5x=-70 | | 2j+3=5j-12 | | x(42)=462 | | X+2=5+2/x | | 36=2(7)+2w | | x/15=41 | | √x3+5=46 | | 4x-5+6x=-5+10 | | 25=5i+13 | | 6y+2=81 | | 4h-7=7 | | 5x-(x-118)=6-2(x+15) | | (X+5)-2(x+3)=1 | | -8(u-1)=6u-34 | | 2.2x=4 | | 1/4g+3=5 | | -3.69=s/3 | | 3/4x-1/3=7/12+5/6x | | n/20=31 | | 1/2f+3=8 | | 2=5a=17 | | 180=(10x-26)+(7x+10) | | 453=g+-322 | | -2=4-x-4 | | 180=10x-26+7x+10 | | 45.2=2x+25.6 |